Factors influencing virtual team performance in Malaysia - Tan, Chong King; T., Ramayah; Teoh, Ai Ping; Cheah, Jun Hwa (Emerald Publishing, 2019)
Purpose Virtual teams had become a fundamental way to conduct business for organizations to remain competitive and sustain in a global environment. Organizations which willing to understand what makes virtual teams more effective can likely accrue positive results from virtual teams. Hence, the purpose of this paper is to investigate what are the factors that impact the performance of virtual team. This study highlights factors that influence virtual team performance, which not been widely studied in developing countries (i.e. Malaysia). This study tests the impact of six factors (coordination, communication, relationship building, cohesion, trust and reward) on team performance.